Expert recommendations for setting and adjusting airway pressure release ventilation based on clinical experience and basic science evidence - Nieman, Gary F.; Bates, Jason H. T.; Andrews, Penny L.; Rose, Louise; Shiber, Joseph; Araos, Joaquin; Aurelien, Ledoux; Madden, Maria; Manougian, Toni; Satalin, Josh; Varpula, Tero; Al-khalisy, Hassan; et al. (Frontiers in Medicine, 2026)
BackgroundWe conducted a roundtable discussion and provided evidence-based guidance on the setting and adjustment of Airway Pressure Release Ventilation (APRV) in adult patients with acute respiratory distress syndrome (ARDS).MethodsA panel of clinicians and basic scientists with extensive experience in lung physiology and using APRV was assembled to provide expert consensus guidance. The panel first established and agreed upon guiding principles for optimal APRV settings. To support consensus discussions, we then reviewed the literature on the physiological basis of APRV as a lung-protective ventilation strategy, as well as published APRV research. Finally, we held a one-day meeting and conducted robust, iterative consensus discussions using the Nominal Group Technique to reach agreement on the optimal APRV settings. This work represents an Expert Recommendation and Position Statement rather than a formal consensus guideline. The recommendations were developed through iterative expert discussions that integrated extensive clinical experience with supporting basic science evidence on time-controlled ventilation and alveolar mechanics. Recommendations were based on expert experience with APRV in the intensive care unit and supported by published animal and clinical studies.ResultsConsensus on initial APRV settings for acute lung injury (ALI) such as ARDS or disorders of normal or increased elstance was as follows: set the upper airway pressure (PHigh) to either plateau or peak inspiratory pressure when transitioning from volume control or pressure control/dual control, respectively; set the duration of PHigh (THigh) to match the current respiratory rate on conventional ventilation; set lower airway pressure (PLow) to 0 cmH2O; and calculate duration of PLow (TLow) using the equation Peak Expiratory Flow x 75% = Termination of Expiratory Flow. Other recommendations included titrating these settings in response to changes in lung physiology and reaching consensus on injurious APRV settings that could impair gas exchange or cause lung instability.ConclusionThe panel developed a protocol for adjusting the four APRV settings based on expert experience and solid clinical and scientific evidence for patients with ALI and ARDS, or disorders of normal or increased elastance. Optimizing the lung-protective settings in APRV mode can improve patient outcomes.